Examining the complexities of increasing park access in two Latinx neighbourhoods. Issue 12 (2nd December 2019) - Fernandez, Mariela; Harris, Brandon; Becerra, Marisol
ABSTRACT: Although research has shown that park resources and other open green spaces lead to numerous benefits, progress in increasing access to parks and open green space has also come with unexpected challenges, which have received less attention in the scholarly literature. The purpose of this study was to examine the contradictory effects of improved park and green space access in the cases of two newly created sites in Chicago, IL. The study focused on the neighbourhoods of Little Village and Humboldt Park, both of which experienced the integration of a new public park or greenway. The data analysis revealed several health benefits associated with the new park or greenway, but also revealed some unintended consequences (i.e. crime, rising taxes, and gentrification) associated with the increased access. The practical and theoretical implication associated with the study findings are discussed.